Road Infrastructure Development in Jambi Province During the New Order Period - Musdalifah, Musdalifah; Hartatik, Endah Sri; Rinardi, Haryono (Indonesian Historical Studies, 2024)
This article examines the development of road infrastructure in Jambi Province during the New Order era and its impact on the socioeconomic aspects of the local community. The study employs a historical research methodology, encompassing heuristics, source criticism, interpretation, and historiography. The development initiatives of the New Order period were pivotal in the expansion of road infrastructure in Jambi Province. This infrastructure development, particularly road construction, was integrated into the Five-Year Development Plans (Repelita) and implemented in phases. For Jambi Province, the Repelita aimed to accelerate development and bridge the gap with other regions. This study analyzes the impact of infrastructure development, specifically focusing on its role in facilitating economic activity and the mobility of people and goods. The findings reveal that infrastructure development contributed significantly to social and economic life, including increased agricultural yields, diversification of professions, the emergence of new productive areas, changes in demographics and multi-ethnic diversity, and an overall improvement in the quality of life for the population.